On Vertex Covering Transversal Domination Number of Regular Graphs - R. Vasanthi; K. Subramanian (The Scientific World Journal)
A simple graph G=(V,E) is said to be r-regular if each vertex of G is of degree r. The vertex covering transversal domination number γvct(G) is the minimum cardinality among all vertex covering transversal dominating sets of G. In this paper, we analyse this parameter on different kinds of regular graphs especially for Qn and H3,n. Also we provide an upper bound for γvct of a connected cubic graph of order n≥8. Then we try to provide a more stronger relationship between γ and γvct.